1998
DOI: 10.1164/ajrccm.158.6.9712135
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics, Respiratory Functional Parameters, and Outcome of a Two-Hour T-Piece Trial in Patients Weaning from Mechanical Ventilation

Abstract: The discrepancy in results from different studies regarding outcome of weaning from mechanical ventilation may be due to several factors such as the differences in patient populations and weaning indexes used. In order to analyze the clinical characteristics and weaning indexes in patients undergoing a 2-h T-piece weaning trial and the relationship between the etiology of acute respiratory failure (ARF) and the outcome of this weaning trial, we prospectively studied 217 patients receiving mechanical ventilatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
149
6
5

Year Published

2000
2000
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 379 publications
(187 citation statements)
references
References 39 publications
13
149
6
5
Order By: Relevance
“…Published November 28, 2011 Extubation failure is defined as the reinstitution of respiratory support from 24 to 72 h following the scheduled extubation. This condition occurs in 2 to 25% of extubated patients (1)(2)(3). Extubation failure increases the incidence of mortality, pneumonia, number of days in the intensive care unit (ICU) and hospital, time spent on mechanical ventilation (MV), hospital costs, and the need for a tracheostomy (4)(5).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Published November 28, 2011 Extubation failure is defined as the reinstitution of respiratory support from 24 to 72 h following the scheduled extubation. This condition occurs in 2 to 25% of extubated patients (1)(2)(3). Extubation failure increases the incidence of mortality, pneumonia, number of days in the intensive care unit (ICU) and hospital, time spent on mechanical ventilation (MV), hospital costs, and the need for a tracheostomy (4)(5).…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have demonstrated an increased incidence of reintuba-tion, pneumonia, and prolonged MV among such patients (2)(3)(4)(5)7,9,14,15).…”
Section: Introductionmentioning
confidence: 99%
“…The current predictive indices do not distinguish patients who, after a satisfactory SBT, will be reintubated from those who will be successfully extubated 3,19 .…”
Section: Discussionmentioning
confidence: 67%
“…Extubation failure (EF) was associated with higher mortality rate (70%). Several studies show that EF is associated with increased mortality 2,3,6,[18][19][20] . According to Epstein et al 6 , the mortality rate in patients with EF was 43% compared to 12% among those with weaning success (p < 0.0001).…”
Section: Discussionmentioning
confidence: 99%
“…Clearly, the present threshold values for weaning indices need to be tested prospectively in future studies in COPD patients, which should also take into account the effect of duration of mechanical ventilation on weaning outcome [1]. However, the results of a recent study of VALLERDU Á et al [16] suggest that the present threshold value for fR/VT, which is lower than that proposed by YANG and TOBIN [1] (84 versus 100 breaths . min -1 .…”
Section: Discussionmentioning
confidence: 75%